Estratégia como prática social e discursiva: um estudo sob a perspectiva da análise crítica do discurso - Valeria da Gloria Pereira Brito (2013)
The objective of this thesis was to unravel the process of socio-discursive construction of the strategies practiced by the Family Producers Cooperative of Poço Fundo, particularizing the social-historical aspects which mark this process. We seek to: a) recover the social-historical context in which the focused cooperative organization is inserted, specializing in the discourse order which has and still marks the construction of organizational strategies; b) analyze the production, distribution and consumption processes of this discourse order, evidencing the political and ideological specificities of this process; c) observe and interpret the effects of the discourse order in strategy formation, focusing their discursive and non-discursive repercussions of the strategic practices of the analyzed cooperative organizations. We opted for an interdisciplinary perspective which remitted to centralizing the language of organization construction, applying the Discourse Critic Analysis as a theoretical-methodological approach. We started with strategizing as a social and discursive practice, that is, we formulated questions which served as a starting point for the critical exam of language corpus constructive texts, delimited for research purpose. The historical experience referred to in this thesis was marked for singular strategic specificities which emerged from the appropriation of a discourse order socially constituted in a macro-social market context by social, politic, economic and cultural transformations. Our ontological and epistemological choices allow us to critically analyze the collective action strategies, sustainable familiar organic production and the insertion into the market fair trade (MFT). We conclude that the strategies are discursively constructed organizational phenomenon of which nature is marked by the relation between social structure and collective action. This conception implies in recognizing that strategies are not located in the organizations nor are they property of strategists. They are, dialectically, the product and the producer of a discourse formed, distributed and consumed by collective subjects. We found that strategizing maintains a close relation to the local knowledge constructed by socially organized agents which appropriate themselves of a macro-social discourse order market for different ideologies. Our research also demonstrates the analytical potential of the DCA for the strategizing studies, differentiating from those which approach the micro-sociological aspects. By means of the DCA it was possible to understand the formation, legitimation, naturalization or normalization processes of strategizing as socio-discursive practices. Thus, we conclude that strategizing: i) is anchored in the macro-social or social-historical movements; ii) reproduces political (power relations) and ideological elements, of which genesis is tied to a specific discourse order; iii) keeps the inter-discursive mark which is revealed in a social and organizational language corpus; iv) presents a relational character, sheltering elements or discursive and non-discursive practices (material and social); v) are socially constructed, legitimized and naturalized by the different political and symbolical mechanisms historically constructed and situated in time and space. We also present the agenda of research applied to the organizational field, including the cooperative organizations.